Pengaruh Annoyance Media Sosial Pada Niat Beli Konsumen dan Kesadaran Merek - Ahmad noor islahudin; Nina Ramadhani Wulandari (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2019)
Online Shop Nina's Cake is one of the online cake shop that has four years of pioneering early marketing in the year 2012 only use BBM and facebook. And now more focus on Instagram as a means of online communication that its marketing every year increases and also annoyance increases every year. This study aims to determine the effect of annoyance in the use of social media on brand awareness and purchase intention of consumers study online cake shop Nina's Cake on Instagram. Data analysis technique used is path analysis which at significance level 5% by using questioner as primary data. The study population was the customer of Nina's Cake user in Instragram. Of the population were sampled 100 people. The results showed that annoyance significantly influenced brand awareness by 61.8%. While the annoyance on consumer purchase intention by 30,9% and brand awareness on consumer purchase intention significantly equal to 41,7%